Economic impacts of information access through public policies: impacts of rural extension and internet access on Brazilian agricultural production - Rocha Junior, Adauto Brasilino (2021)
In this dissertation I analyze two policy issues in information access and agricultural productivity. The first one is the impact of the technical assistance and rural extension (TA) access on the production of Brazilian family farmers, and the second one is the impact evaluation of a real case of public policy proposed to expand the internet access in Brazilian countryside. The Output Distance Function is the parametric approach applied to model the production possibilities frontier and the technical efficiency level of the agriculture for Brazilian municipalities, and impacts on agricultural production due to the technical assistance access for family farmers, and internet access for all farmers, are estimated in each paper. The results from both studies constitute methodological background for the estimation of impacts on production from Output Distance Functions, and evidence of the role of technical assistance and internet access for the Brazilian agricultural production.